SPECTRAL-TEMPORAL PROFILE ANALYSIS OF MAIZE, SOYBEAN AND SUGARCANE BASED ON OLI/LANDSAT-8 DATA - Montibeller, Bruno; Sanches, Ieda Del'Arco; Luiz, Alfredo José Barreto; Gonçalves, Fabio; Aguiar, Daniel Alves de (REVISTA DE AGRICULTURA, 2019)
Remote sensing (RS) technology is a viable complementary alternative to current agriculture surveying methods. RS data spectral information is the main variable used for several purposes, such as crop type identification. However, different management practices (MP) adopted in crop cultivation may alter its spectral characteristics. The objective of this work is to analyze the spectral-temporal profile (STP) variation of soybean, maize and sugarcane cultivated under different MP. We used time series of the six spectral bands of the OLI/Landsat-8 sensor and of two vegetation indexes (VI) to investigate the intraspecific variation (same crop specie) and the interspecific variation (different crop species). We applied hierarchical cluster analyses to determine the crop´s STP variation. The bands results were more efficient than the VI. This shows that despite the widely use of VI, better results are retrieved when using the bands STP, which also allows differentiating and analyzing crops cultivated under different MP.